The link between bone-derived factors osteocalcin, fibroblast growth factor 23, sclerostin, lipocalin 2 and tumor bone metastasis - Martiniakova, Monika; Mondockova, Vladimira; Biro, Roman; Kovacova, Veronika; Babikova, Martina; Zemanova, Nina; Ciernikova, Sona; Omelka, Radoslav (Frontiers in Endocrinology, 2023)
The skeleton is the third most common site of metastatic disease, which causes serious bone complications and short-term prognosis in cancer patients. Prostate and breast cancers are responsible for the majority of bone metastasis, resulting in osteolytic or osteoblastic lesions. The crosstalk between bone cells and their interactions with tumor cells are important in the development of lesions. Recently, both preclinical and clinical studies documented the clinical relevance of bone-derived factors, including osteocalcin (OC) and its undercarboxylated form (ucOC), fibroblast growth factor 23 (FGF23), sclerostin (SCL), and lipocalin 2 (LCN2) as prognostic tumor biomarkers and potential therapeutic targets in bone metastasis. Both OC and ucOC could be useful targets for the prevention of bone metastasis in breast cancer. Moreover, elevated OC level may be a metastatic marker of prostate cancer. FGF23 is particularly important for those forms of cancer that primarily affect bone and/or are characterized by bone metastasis. In other tumor entities, increased FGF23 level is enigmatic. SCL plays a significant role in the pathogenesis of both osteolytic and osteoblastic lesions, as its levels are high in metastatic breast and prostate cancers. Elevated expression levels of LCN2 have been found in aggressive subtypes of cancer. However, its role in anti-metastasis varies significantly between different cancer types. Anyway, all aforementioned bone-derived factors can be used as promising tumor biomarkers. As metastatic bone disease is generally not curable, targeting bone factors represents a new trend in the prevention of bone metastasis and patient care.